0426 Shallower sleep depth in the laboratory is not related to insomnia severity. (25th May 2022) - Larson, Olivia; Younes, Magdy; Weljie, Aalim; Sengupta, Arjun; Gehrman, Philip
Abstract: Introduction: In insomnia, classical sleep scoring parameters are often uncorrelated with symptom severity and may not fully capture more subtle alterations in the polysomnogram (PSG) that could contribute to clinical symptoms. The odds ratio product (ORP) is a well-validated, continuous index of sleep depth (range 0=deep sleep; 2.5=full wakefulness) that offers an alternative to traditional staging. It is unknown whether ORP is related to self-reported insomnia severity. We hypothesized that individuals with insomnia would exhibit higher ORP values than healthy controls (reflecting less deep sleep) which would be associated with greater insomnia severity. Methods: This is a secondary analysis of data from a study in which n=15 participants with chronic insomnia disorder and n=15 age- and sex-matched healthy controls completed an in-laboratory protocol (N=30; 66% female; 36±8 years; 63% White). Participants had their sleep monitored with in-lab PSG. The Insomnia Severity Index (ISI) was used to estimate sleep disturbance severity. PSG were used to calculate classical sleep scoring parameters as well as the average ORP in each sleep stage. Independent samples t-tests compared means between the insomnia and healthy control groups and Pearson's correlations assessed relations between PSG/ORP outcome measures and ISI scores. Results: The insomnia group's mean (SD) ISI score was 14.13 (6.00) and significantly higher than the control group's (1.73 (2.37); corrected p < 0.001). There were no statistically significant between-group differences for classically-scored sleep parameters or average ORP values after correcting for multiple comparisons. Interestingly, means for the insomnia group's average ORP values tended to be higher than those of the control group's. ISI scores were not significantly associated with average ORP values across or within groups. Conclusion: Insomnia does not appear to be associated with alterations in global sleep depth when measured in a laboratory setting, but there is a need to conduct more detailed analyses on patterns across the night. Support (If Any): Merck, Inc. Investigator Studies Program